PEMETAAN PHYLUM ECHINODERMATA (KELAS ASTEROIDEA) DI ZONA LITORAL PANTAI PASIR PUTIH SITUBONDO - Purwandari, Anggraini Ratih (Universitas PGRI Argopuro Jember, 2023)
Class Asteroidea is a member of the phylum Echinodermata Asteroidea with high diversity, diversity will be found the similarities and differences that can be used as a key identification and classification. Pasir putih Situbondo beach has many invertebrate animals, particularly Asteroidea class that can be used to research about their abundance. The problems that arise are animals Echinodermata (classes Asteroidea ) What are some which can be found on the shore of Pasir Putih Situbondo beach can be used as a source data about their abundance. The results showed that the white sand beach Situbondo is found one type of the class Asteroidea namely Linckia laevigata acquisition this study of transects 1 to 15 only one transect contained starfish is on transect 14 wherein the transects , measuring 100 m sea littoral zone. Reason discovery of starfish on the shore of Pasir Putih Situbondo beach slightly due to limited types of starfish Asteroidea because in this month is going east wind season so that the starfish is hard to find.